Clinical Characteristics and Neonatal Outcomes of Pregnant Patients With COVID-19: A Systematic Review - Islam, Md. Mohaimenul; Poly, Tahmina Nasrin; Walther, Bruno Andreas; Yang, Hsuan Chia; Wang, Cheng-Wei; Hsieh, Wen-Shyang; Atique, Suleman; Salmani, Hosna; Alsinglawi, Belal; Lin, Ming Ching; Jian, Wen Shan; Jack Li, Yu-Chuan (Frontiers in Medicine, 2020)
Background and Objective: Coronavirus disease 2019 (COVID-19) characterized by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has created serious concerns about its potential adverse effects. There are limited data on clinical, radiological, and neonatal outcomes of pregnant women with COVID-19 pneumonia. This study aimed to assess clinical manifestations and neonatal outcomes of pregnant women with COVID-19. Methods: We conducted a systematic article search of PubMed, EMBASE, Scopus, Google Scholar, and Web of Science for studies that discussed pregnant patients with confirmed COVID-19 between January 1, 2020, and April 20, 2020, with no restriction on language. Articles were independently evaluated by two expert authors. We included all retrospective studies that reported the clinical features and outcomes of pregnant patients with COVID-19. Results: Forty-seven articles were assessed for eligibility; 13 articles met the inclusion criteria for the systematic review. Data is reported for 235 pregnant women with COVID-19. The age range of patients was 25-40 years and the gestational age ranged from 8 to 40 weeks plus six days. Clinical characteristics were fever (138/235 [58.72%]), cough (111/235 [47.23%]), sore throat (21/235[8.93%]). 156 out of 235 (66.38%) pregnant women had cesarean section and 79 (33.62%) had a vaginal delivery. All the patients showed lung abnormalities in CT scan images and none of the patients died. Neutrophil cell count, C-reactive protein (CRP) concentration, ALT, and AST were increased but lymphocyte count and albumin levels were decreased. Amniotic fluid, neonatal throat swab, and breastmilk samples were taken to test SARS-CoV-2 and found negative results. Conclusions: Our study findings show that the clinical, laboratory and radiological characteristics of pregnant women with COVID-19 were similar to general populations. Our study also indicated that COVID-19 is not an indication of either cesarean delivery or vertically transmission. Future study is needed to confirm or refute these findings with a large number of sample sizes and long-term follow-up period.